A sharia compliance audit of murabahah contracts: Investigating price transparency and gharar risk mitigation in MSMEs - M. Robi’in; Deden Ramdhani; Muhammad Restu Maulana (Institute of Accounting Research and Novation (IARN), 2025)
Installment sale transactions frequently raise potential issues regarding non-compliance with Sharia principles, making the murabahah contract a vital Islamic solution emphasizing the honesty and transparency of the cost price. However, implementing this contract in the Micro, Small, and Medium Enterprises (MSME) sector often faces practical challenges, particularly in fulfilling the essential requirement of cost disclosure. This study aims to analyze the Sharia compliance of the murabahah implementation at Toko Raina Collection and to describe the mitigation efforts for the resulting issues. The methodology employs a qualitative descriptive approach with a case study design, utilizing observation and in-depth interviews with the store owner and customers for data collection. The findings indicate that the installment sales practice fulfills the general pillars of Islamic trade, such as ‘aqidain (parties) and sighat (offer and acceptance), but fails to meet the essential murabahah condition of disclosing the original cost price. The owner does not itemize the cost but sets a final total sale price, causing the contract to substantively shift to an ordinary deferred payment sale (bai' bitsaman ajil). This non-compliance is implicitly mitigated through setting a reasonable profit margin to maintain customer satisfaction (ridha). The study concludes that the practice is not kaffah (perfect) as murabahah. The research contributes empirical insight into the implementation gap of murabahah at the MSME level and offers recommendations for achieving full Sharia compliance.